Efficacy of Cold Atmospheric Plasma Against Methicillin‐Resistant Staphylococcus aureus Biofilms: A Systematic Review of In Vitro Studies. - Shoorgashti, Reyhaneh; Dehghan Ghanatkaman, Faezeh; Baghizadeh, Sana; Ehsani, Sarah Sadat; Lesan, Simin; Ebrahimi, Hooman; Banerjee, Baisakhi (BioMed Research International, 2026)
Background: Methicillin‐resistant Staphylococcus aureus poses a serious threat to global health due to its resistance to conventional antibiotics and its ability to form resilient biofilms. Cold atmospheric plasma has emerged as a promising alternative for microbial biofilm inactivation. Objective: To systematically evaluate the in vitro efficacy of cold atmospheric plasma in disrupting or eradicating methicillin‐resistant Staphylococcus aureus biofilms and to identify factors influencing treatment outcomes Methods: A comprehensive search was conducted in five databases (PubMed/MEDLINE, Embase, Scopus, Web of Science, and Google Scholar) for in vitro studies published up to July 2025. Eligible studies assessed cold atmospheric plasma effects on methicillin‐resistant Staphylococcus aureus biofilms. Data were extracted on study characteristics, cold atmospheric plasma device parameters, exposure conditions, and microbial outcomes. Risk of bias was assessed using a modified version of the ToxRTool. Results: Seventeen in vitro studies were included. Most studies originated from European countries (n = 10), with a peak in publications observed in 2021. Dielectric barrier discharge and plasma jets were the most common devices. Air‐based plasmas were the most commonly used in 12 studies, followed by helium. All studies reported cold atmospheric plasma‐mediated reductions in methicillin‐resistant Staphylococcus aureus biofilm load, with log10 colony‐forming unit reductions ranging from 1 to > 6, depending on exposure time, surface material, and device configuration. Several studies demonstrated near‐complete biofilm eradication within minutes. Synergistic effects were observed when cold atmospheric plasma was combined with antibiotics. Conclusions: These findings suggest that cold atmospheric plasma may have potential as an adjunctive strategy for biofilm‐related infection control, although further standardized and clinically relevant studies are needed.